Analysis of the Socio-Economic Conditions of Mustahik in Karang Pule Village, Sekarbela District - Imam Maulana Malik Ibrahim; Muhammad Irwan (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
This research aims to analyze the socio-economic conditions of mustahik in Karang Pule sub-district, Sekarbela sub-district. This research uses a qualitative approach with descriptive methods. The data collection techniques used were observation, interviews and documentation, while the data validity method used was the triangulation method. The results of this research are that the socio-economic conditions of mustahik in Karang Pule sub-district, Sekarbela sub-district can be seen from their level of education, type of work and income. The average mustahik's education in Karang Pule sub-district is at elementary school level, so it affects their work because many mustahik don't have a diploma, which is an obstacle to working. His job is impossible in Karang Pule sub-district only as a vegetable trader, laborer and other low-level jobs. However, with zakat and assistance from Baitul Askhiya, his family's economy could slowly recover.